Effect of Carbon‐Based Materials on the Early Hydration of Tricalcium Silicate. Issue 6 (17th March 2016) - Sobolkina, Anastasia; Mechtcherine, Viktor; Bergold, Sebastian T.; Neubauer, Jürgen; Bellmann, Cornelia; Khavrus, Vyacheslav; Oswald, Steffen; Leonhardt, Albrecht; Reschetilowski, Wladimir
Abstract : Two types of carbon‐based materials, i.e., mesoporous carbon and HNO3 ‐oxidized carbon nanotubes, with nearly the same specific surface area and abundant in surface oxygen‐containing functional groups were selected in order to examine their effect on the hydration of tricalcium silicate (C3 S), the main portland cement component, in early stages. Different methods, including XPS and TG‐MS analyses, electrokinetic potential measurements, as well as determination of adsorption capacity for calcium ions from aqueous solutions, were used to investigate the physicochemical surface properties of the selected carbon‐based materials. It was found that the carbon‐based materials with high specific surface area and rich in oxygen‐containing functional groups on their surfaces have a catalytic effect on early C3 S hydration. It was observed that the modification of C3 S paste with the selected materials added in high concentrations (1 wt% and higher) led to an increase in the rate and degree of C3 S hydration in the early stages. The mechanism of early C3 S hydration accelerated by carbon‐based materials rich in surface functional groups was clarified by the example of the mesoporous carbon. It was found that the oxygen‐containing functional groups present on the carbon surface have both an influence on the content of calcium ions in the aqueous phase of the C3 S paste and an indirect positive effect in relation to the specific surface of C3 S.